A D-π-A-π-A metal-free organic dye with improved efficiency for the application of solar energy conversion. (November 2016) - Luo, Geng-Geng; Lu, Hui; Wang, Yong-Heng; Dong, Jia; Zhao, Yang; Wu, Rui-Bo
Abstract: A novel metal-free D-π-A-π-A based organic photosensitizer, with carbazole as electron donor; benzothiadiazole as auxiliary electron withdrawing unit; acetylene and benzene as linker; and cyanoacrylic acid as anchoring group, has been successfully synthesized and effectively employed in the development of solar energy conversion of photovoltaic devices and solar hydrogen generation. In the solar energy conversion systems, comparisons were made with a simple reference D-π-A sensitizer. The results show that the new D-π-A-π-A dye has greater potential in the light-to-fuel conversion (ΦH2  = 5.56% for the new dye vs ΦH2  = 0.12% for the reference dye) than light-to-electricity conversion ( η  = 3.50% for the new dye vs 1.14% for the reference dye). Graphical abstract: Highlights: A D-π-A-π-A based organic dye has been successfully synthesized and characterized. The dye showed a multifunctional property in both DSC and solar fuel generator. The dye showed better performance in the light-to-fuel conversion.